1975
DOI: 10.1161/01.res.37.5.664
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the chemoreflex and the pulmonary inflation reflex in the regulation of coronary circulation in conscious dogs.

Abstract: The interaction of chemoreflex and pulmonary inflation reflex control of the coronary circulation was examined in conscious dogs by comparing the responses to chemoreflex stimulation (intracarotid injection of nicotine) when ventilation was allowed to increase with those when ventilation was controlled. The responses were also compared with those elicited by both forced mechanical and spontaneous hyperinflation. When the heart rate was constant, intracarotidly administered nicotine induced an increase in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

1978
1978
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 33 publications
2
33
1
Order By: Relevance
“…The coronary vasodilatation seen in the present study is similar to that which has PULMONARY CHEMOREFLEX AND CORONAR Y RESISTANCE 287 been observed previously during carotid sinus nerve stimulation (Hackett, Abboud, Mark, Schmid & Heistad, 1972), peripheral chemoreceptor stimulation (Hashimoto, Igarashi, Uei & Kumakura, 1964;Vatner & McRitchie, 1975;Vatner, 1983;Murray, Lavallee & Vatner, 1984), carotid sinus baroreceptor stimulation (Ito & Feigl, 1985), and the Bezold-Jarish reflex (Feigl, 1975). Further, the neurohumoral basis for the changes in coronary resistance evoked by capsaicin in the present study is comparable to that seen in previous studies.…”
Section: G a Ord Wa Y And K H Pitettisupporting
confidence: 91%
“…The coronary vasodilatation seen in the present study is similar to that which has PULMONARY CHEMOREFLEX AND CORONAR Y RESISTANCE 287 been observed previously during carotid sinus nerve stimulation (Hackett, Abboud, Mark, Schmid & Heistad, 1972), peripheral chemoreceptor stimulation (Hashimoto, Igarashi, Uei & Kumakura, 1964;Vatner & McRitchie, 1975;Vatner, 1983;Murray, Lavallee & Vatner, 1984), carotid sinus baroreceptor stimulation (Ito & Feigl, 1985), and the Bezold-Jarish reflex (Feigl, 1975). Further, the neurohumoral basis for the changes in coronary resistance evoked by capsaicin in the present study is comparable to that seen in previous studies.…”
Section: G a Ord Wa Y And K H Pitettisupporting
confidence: 91%
“…Thus, it is possible that the increase in coronary flow could have been responsible for the increase in contractility. However, this mechanism seems unlikely in view of the experiments after beta adrenergic blockade where the reflex coronary vasodilatation still occurs (13), but the inotropic response was abolished. If the increase in flow produced the inotropic response, then the response should not have been abolished by beta blockade.…”
Section: * Discussionmentioning
confidence: 97%
“…It is known that stimulation of the carotid chemoreceptor reflex elicits reflex coronary vasodilatation (13). It has also been reported that an increase in coronary flow, per se, may increase myocardial contractility (24).…”
Section: * Discussionmentioning
confidence: 99%
See 2 more Smart Citations